Environmental and social aspects of the mining water in Bulgaria - Simova Iskra; Velichkova Rositsa; Pavlova Yoana; Zelenakova Martina (E3S Web of Conferences)
The mining industry in Bulgaria is a key economic driver, with extensive mineral resources and over 527 active concessions, making it a leader in Europe. However, the environmental and social impacts of the mining activities are considerable, especially in the context of the European Union’s Green Deal and the global push for sustainable development. The paper presents a review of the environmental consequences of mining, particularly on water pollution and acid mine drainage (AMD), which pose persistent risks to ecosystems and public health. The study also explores current water management practices, treatment methods, and regulatory efforts, as well as the role of Corporate Social Responsibility (CSR) the Sustainable Development Goals, and public perception. The paper underscores the urgent need for improved policy coherence, community engagement, and innovative environmental technologies to align Bulgaria’s mining sector with the broader goals of climate neutrality and sustainable development.